การสกัดระดับจุลภาคแบบกระจายสำหรับการตรวจวัดตะกั่วและดีบุกในอาหารกระป๋องประเภทน้ำ - ทิพย์สุดา ทับโพธิ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2017)
Food processing and preservation can cause unintended contamination in food. This project developed a dispersive liquid-liquid microextraction (DLLME) method for simultaneous extraction of Pb2+ and Sn2+ for the detection by inductively coupled plasma – optical emission spectroscopy (ICP-OES) in aqueous based canned foods. The Codex Committee Food Additives and Contaminants (CCFAC) and World Health Organization (WHO) set maximum concentration limits for Pb²⁺ and Sn²⁺ at 1 and 250 ppm, respectively. Simultaneous extraction conditions are: 8.0 % (w/w) sodium diethyldithiocarbamate (DDTC) as a chelating agent, 500 μL of chloroform as extraction solvent, 800 μL of methanol as disperser solvent, 3 minutes of centrifuge and 45 °C of extraction temperature. The optimized method provides 43.3 and 4.05 folds enrichment for Pb²⁺ and Sn²⁺, respectively.